URIP IKU URUP : PEMBERDAYAAN MASYARAKAT DI TENGAH PANDEMI COVID-19 MELALUI PAWON URIP - Sukma Irdiana; Kusnanto Darmawan; Kurniawan Yunus Ariyono (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2021)
The Covid-19 pandemic has been going on since the beginning of 2020. During the pandemic, people are expected to stay at home, unless there is a need that cannot be left behind. Staying at home really makes people bored, especially children. However, the problem of staying at home is not just boredom, but also an increase in expenses at home for the family. Not only that, layoffs or layoffs for employees to factory workers are a new problem for a family. This is all because the level of transmission of this virus is increasingly widespread. For this reason, the TP PKK Lumajang Regency made an innovation, namely Pawon Urip. This innovation made the community service team of STIE Widya Gama Lumajang together with the Pasrujambe District government participate in the success of this Pawon Urip program. In this community empowerment, three activities were carried out including: 1) Outreach to the community about community service activities by supporting a Lumajang Regency government program. 2) Training for the community on vegetable cultivation, marketing and financial management. 3) Monitoring the results of training provision and seeing to what extent the level of success of these community empowerment activities. The results of this community empowerment are very satisfying. It is proven by the community that they can apply the results of cultivation training, market and manage finances well. So that the community service team felt that they could release the people of Munggir Hamlet, Pasrujambe Village, Pasrujambe District well.